1998
DOI: 10.1017/s0007114598001111
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of α- and β-carotene is affected by gut microflora in the rat

Abstract: The present study examined whether the intestinal microflora could affect the bioavailability and vitamin A activity of dietary aand b-carotene in the rat. In the first set of experiments, we used conventional, germ-free (axenic), and human-flora-associated (heteroxenic) rats. In a second series, conventional rats were treated with either an antibiotic mixture or a potent inhibitor of gastric secretion (Omeprazole). All animals were first depleted of vitamin A over 4 weeks and then were fed on a sterilized die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…However, other investigators have also noted low and variable recoveries of BC in faeces after a single oral dose in other species (Lederman et al., 1998; Ho et al., 2009). BC may also be destroyed in the GI tract by chemical and microbial degradation, decreasing faecal excretion (Yeum and Russell, 2002); for example, it was shown that BC excretion was higher in germ‐free rats compared with those with normal intestinal microflora (Grolier et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have also noted low and variable recoveries of BC in faeces after a single oral dose in other species (Lederman et al., 1998; Ho et al., 2009). BC may also be destroyed in the GI tract by chemical and microbial degradation, decreasing faecal excretion (Yeum and Russell, 2002); for example, it was shown that BC excretion was higher in germ‐free rats compared with those with normal intestinal microflora (Grolier et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that plant lipoxygenases present in feed plants could quickly destroy BC and lutein in vitro in bovine rumen fluid [72]. In addition, bioavailability of BC was higher in germ-free rats compared to those with normal gut microflora [73]. …”
Section: Bioavailability Of Carotenoidsmentioning
confidence: 99%
“…However, cattle and their close relatives appear to be unique among the species of the family Bovidae, many of whom have been designated nonaccumulators of carotenoids despite consuming moderate to high dietary levels (see “other Artiodactyla”). BC can be destroyed by rumen bacteria [72] and lipoxygenases present in some forage plants [73], and these factors may contribute to variability of responses to BC consumed by cattle and other herbivores.…”
Section: Species Differences In β-Carotene Metabolismmentioning
confidence: 99%
“…Additionally, antibiotic treatment is a very simple method used to determine the impact of the gut microflora on drug metabolism [28,29,[35][36][37]. Thus, the analysis of metabolic profiles for antibiotic-treated animals might be valuable, to understand the gut microflora's role in host physiology and metabolism.…”
Section: Controlmentioning
confidence: 99%